Ultimate x-men (2001), volume 9 ebook The tempest. - Vaughan, Brian K. (Ultimate X-Men (2001), 2012)
Collects Ultimate X-Men #46-49. The X-Men have become more than a team. They've become a family. And the death of one of their own leaves the remaining X-Men struggling to deal with the loss. And even before a moment of silence can pass, the mysterious Mr. Sinister arrives, intent on giving the X-Men a lot more to mourn! Author: Brian K. Vaughan. Illustrator: Brandon Peterson. © 2019 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com